Survey Paper on DSDV and AODV Routing Protocol of MANET - Dkhar, PW; Khongthaw, R (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad hoc network is also known as MANET. MANET is a collection of wireless device which dynamically form a network topology without any pre-existing network infrastructure. In MANET, mobile node can move freely from one place to another and thus network topology is kept changing every time because of self-organization and self-configuration. In MANET, nodes can communicate with each other without any centralized devices and they will be able to exchange information between themself. All nodes act as router between itself to receive packet and forward to itss destination. In order to facilitate nodes to communicate each other in network, they use Routing Protocol. The main purpose of Routing protocol is to facilitate communicate between nodes and to forward packet to destination accurately. There are difference types of Routing protocol used in MANET some of them are DSDV and AODV which will be discussed.